2011
DOI: 10.1016/j.molcel.2011.06.005
|View full text |Cite
|
Sign up to set email alerts
|

NanoRNAs Prime Transcription Initiation In Vivo

Abstract: SUMMARY It is often presumed that, in vivo, the initiation of RNA synthesis by DNA-dependent RNA polymerases occurs using NTPs alone. Here, using the model Gram-negative bacterium Pseudomonas aeruginosa, we demonstrate that depletion of the small-RNA-specific exonuclease, Oligoribonuclease, causes the accumulation of 2- to ~4-nt RNAs, “nanoRNAs”, which serve as primers for transcription initiation at a significant fraction of promoters. Widespread use of nanoRNAs to prime transcription initiation is coupled wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
115
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(117 citation statements)
references
References 42 publications
2
115
0
Order By: Relevance
“…Identical initiation and processing sites were described for several transcripts in Arabidopsis thaliana mitochondria (Kü hn et al, 2005). Recently it was demonstrated that the RNA polymerase of the Gram-negative bacterium Pseudomonas aeruginosa may use nanoRNAs as primers for transcription initiation, thus generating primary transcripts with 59 ends similar to processed ones (Goldman et al, 2011). Even though there is no indication that such a process takes place in plastids, a potential similar function of PEP, the bacteria-type RNA polymerase, would explain why no enrichment after TEX treatment of some primary transcripts was observed only in green libraries.…”
Section: Discussionmentioning
confidence: 99%
“…Identical initiation and processing sites were described for several transcripts in Arabidopsis thaliana mitochondria (Kü hn et al, 2005). Recently it was demonstrated that the RNA polymerase of the Gram-negative bacterium Pseudomonas aeruginosa may use nanoRNAs as primers for transcription initiation, thus generating primary transcripts with 59 ends similar to processed ones (Goldman et al, 2011). Even though there is no indication that such a process takes place in plastids, a potential similar function of PEP, the bacteria-type RNA polymerase, would explain why no enrichment after TEX treatment of some primary transcripts was observed only in green libraries.…”
Section: Discussionmentioning
confidence: 99%
“…3 and 5C were performed essentially as described in ref. 29. RNA products generated in these reactions were analyzed by primer extension as described in ref.…”
Section: Methodsmentioning
confidence: 99%
“…RNA products generated in these reactions were analyzed by primer extension as described in ref. 29.…”
Section: Methodsmentioning
confidence: 99%
“…pGpG belongs to the class of "nanoRNA" molecules, which are 2 to 5 nucleotides long. NanoRNAs control gene expression, as they can serve as templates in the promoter-specific initiation of RNA synthesis by DNA-dependent RNA polymerases in vitro and in vivo (388). Thus, the possibility exists that pGpG may have a role in gene expression, presumably under conditions of high c-di-GMP concentrations.…”
Section: Open Questions In C-di-gmp Signalingmentioning
confidence: 99%